Estudio comparativo en los estilos de crianza y su incidencia en el desarrollo socioemocional de los estudiantes de básica superior de la Unidad Educativa Vinces - Carpio Yepez, Milena Lisbeth (2025)
The present research, aims to analyze how different parenting styles influence students' socio-emotional development. A quantitative approach with a correlational design was used, and a sample of 123 students between 12 and 16 years old was selected. Data collection was conducted using three instruments: the "Parenting Styles Test" developed by Pierrehumbert et al. (1996), the "Social and Emotional Skills Assessment Test" created by Goleman (1995), and statistical analysis of the data using SPSS software. The results revealed that the predominant parenting styles in the sample were authoritarian (47%), democratic (35%), and permissive (18%). In terms of socio-emotional development, 60% of students with a democratic parenting style showed more developed socio-emotional skills, while only 25% of students with an authoritarian style and 15% with a permissive style showed adequate social and emotional abilities. The correlation obtained between parenting styles and socio-emotional development was 0.35, indicating a weak positive relationship, but not statistically significant. Although the correlation was not significant, the findings suggest that the democratic parenting style fosters better socio-emotional development in students. In conclusion, the results do not fully support the hypothesis that parenting styles play a decisive role in socio-emotional development, but a positive trend was observed, particularly in the democratic parenting group. The importance of balanced parenting approaches for fostering the emotional well-being of adolescents is emphasized.